2019
DOI: 10.1042/bsr20190013
|View full text |Cite
|
Sign up to set email alerts
|

The association between IL-17 gene variants and risk of colorectal cancer in a Chinese population: A case–control study

Abstract: Interleukin (IL)-17 have been reported to be associated with the pathogenesis of colorectal cancer (CRC). Few studies investigated the association between IL-17 gene polymorphisms and risk of CRC with inconsistent findings. Thus, we recruited 352 CRC cases and 433 controls in a Chinese population and their genotyping was done using polymerase chain reaction-restriction fragment length polymorphism method. Our data showed that IL-17A rs2275913 polymorphism was associated with the increased risk of CRC, while no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In the present study, we inoculated cancer cells into the mice and administered these prophylaxis remedies simultaneously and compared their antitumor effects on day 30. Our in-vivo experiments demonstrated that the PX formula exhibited a stronger antitumor effect than XH treatment, as evidenced by the suppressed tumor size and inhibited levels of IL-17, IL-6, and TNF α , which are the best characterized independent risk factors for CRC [ 22 24 ] and increased IFN γ expression that inhibits the expansion of disseminated colorectal cancer cells [ 25 ]. KEGG analysis showed that PX-target genes were enriched in inflammatory reactions, microbe infections, drug resistance, and carcinogenesis, including CRC and bladder cancer, which was consistent with the RNAseq results of murine CRC models after PX treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we inoculated cancer cells into the mice and administered these prophylaxis remedies simultaneously and compared their antitumor effects on day 30. Our in-vivo experiments demonstrated that the PX formula exhibited a stronger antitumor effect than XH treatment, as evidenced by the suppressed tumor size and inhibited levels of IL-17, IL-6, and TNF α , which are the best characterized independent risk factors for CRC [ 22 24 ] and increased IFN γ expression that inhibits the expansion of disseminated colorectal cancer cells [ 25 ]. KEGG analysis showed that PX-target genes were enriched in inflammatory reactions, microbe infections, drug resistance, and carcinogenesis, including CRC and bladder cancer, which was consistent with the RNAseq results of murine CRC models after PX treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the two genes was consisted of 3 exons and 2 introns and located on the chromosome 6p12.3-q13. The genetic variant of IL-17A rs2275913 was located in the 5'-UTR, involving in the gene transcription regulations and changing the roles of some cytokines[38], IL-17F rs763780 polymorphism was identi ed to be a missense mutation located on the coding region, with the amino acid modifying conversion of His to Arg, resulting in the potential changing of protein expressions and possible cancer risk [25]. An increasing number of studies and meta-analysis were performed to explore associations between the IL-17A rs2275913 and IL-17F rs763780 polymorphisms and virous kinds of malignant tumors in recent years [39][40][41], however, the related ndings for colorectal cancer displayed no consensus.…”
Section: Discussionmentioning
confidence: 99%
“…After then further reading the full text, 298 articles were excluded, including 193 researches unrelated to colorectal cancer, 71 abstracts or systematic reviews, 27 non-case control or cohort studies, 4 prognosis studies of colorectal cancer, 2 without complete genotype frequency or data available data and 1 with duplicated data. Finally, 14 case-control studies including 2599 cases and 2845 controls from 10 papers meeting the inclusion criteria were selected for this meta-analysis [22][23][24][25][26][27][28][29][30][31] Figure 1 . Among included studies, 8 were conducted for IL-17A rs2275913 polymorphism and 6 were conducted for IL-17F rs763780 polymorphism, 6 were regarding to Asian and 8 were regarding to Caucasian.…”
Section: Characteristics Of Publicationsmentioning
confidence: 99%
“… 13 In addition, several studies from different countries found that a single nucleotide polymorphism (SNP) located at the promoter region of the IL17A gene (rs2275913) may affect an individual’s risk of developing CRC. 14 16 However, Bedoui et al. showed that there was no significant association between the rs2275913 polymorphism and CRC risk.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Although a case-control study explored the potential association in a Chinese population, the results needed to be further confirmed due to the small sample size of the study. 14 Hence, in the present study, we not only investigated the association of the rs2275913 polymorphism with CRC risk in a Chinese population by a case-control study method, but also systematically assessed the association of the rs2275913 polymorphism and CRC risk by a pooled analysis method. Overall, we found that the IL-17 rs2275913 polymorphism is associated with CRC risk and may act as a biomarker for predicting susceptibility to CRC.…”
Section: Introductionmentioning
confidence: 99%